Frontal space distance in facial clefts and retrognathia at 11–13 weeks' gestation. (August 2016) - Hoopmann, M.; Sonek, J.; Esser, T.; Bilardo, C. M.; Wagner, P.; Abele, H.; Kagan, K. O.
ABSTRACT: Objective: To examine the frontal space (FS) distance in first‐trimester fetuses with bilateral, unilateral or median cleft lip and palate and in those with retrognathia. Methods: This was a retrospective study using stored two‐dimensional ultrasound images of fetal profiles that were recorded at the time of the nuchal translucency (NT) scan at three prenatal medical centers. Images of 300 normal fetuses and 53 fetuses with facial defects were obtained. To measure the FS distance, a line was drawn between the anterior edge of the mental protuberance of the mandible and anterior edge of the maxilla (MM line) and extended upwards in front of the forehead. The perpendicular distance (FS distance) between the MM line and the skin at the point of largest excursion of the fetal forehead was measured. In cases in which the MM line was located anteriorly to the forehead, the distance was measured in the same fashion but was multiplied by −1. Two operators measured the FS distance twice, independently of each other. FS distances were transformed into Z ‐scores based on the linear relationship with crown–rump length (CRL) in normal fetuses. The distribution of FS distances in fetuses with bilateral, unilateral or median cleft lip and palate and those with retrognathia were compared with that in the normal group using Student's t ‐test. Results: A search of the centers' databases identified 53 abnormal cases including 20, nine and eight with a bilateral, unilateral and median cleft lip and palate, respectively, and 16 cases of retrognathia. In fetuses with bilateral, unilateral and median clefts and those with retrognathia, median delta NT was 1.00 mm, 0.37 mm, 4.00 mm and 0.26 mm, respectively. Among these affected groups, 12 (60.0%), six (66.7%), two (25.0%) and eight (50.0%) fetuses had an abnormal karyotype. In the normal population, FS distance was dependent on CRL measurement (FS = 6.62 − (0.08 × CRL); r  = –0.539; P  < 0.0001). In fetuses with a bilateral and median cleft and in those with retrognathia, FS distance was significantly different from that in the normal population (all P  < 0.0001), however, the difference was not significant in fetuses with unilateral clefts ( P  = 0.103). The respective Z ‐scores of FS distance for fetuses with bilateral, unilateral and median clefts and retrognathia were −9.7 ± 2.0, −3.1 ± 5.1, 8.2 ± 3.4 and −7.3 ± 2.3. Measurements were ≥ 99 th and ≤ 1 st centiles in all but one (98.1%) case. Conclusion: The FS distance appears to be a helpful tool in the detection of facial clefts at 11–13 weeks' gestation. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.